Hubungan Dukungan Keluarga dengan Tingkat Kecemasan pada Pasien Pre Operasi di RS Dr. Soepraoen Malang - Kaslinda Nur Umifa; Merisdawati Mr (Jurnal Kesehatan Amanah, 2023)
Surgery is an invasive procedure that involves opening a part of the body until it is closed again, the planned operation can cause physiological and psychological responses, The psychological response in preoperative patients is anxiety in the patient. This research method is correlation analysis with a cross-sectional design, namely analyzing independent and dependent variables. The population in the study were pre-operative patients at dr. Soepraoen Hospital Malang numbered 20 respondents. The results of the analysis of family support and the level of anxiety in preoperative patients using the Spearman test show a p value of 0.00, indicating that high family support can cause a decrease in preoperative patient anxiety. One of the roles and functions of the family is to provide an affective function to fulfill the psychosocial needs of family members in providing love, the family is the closest support system for the patient. The family is expected to always be involved in planning, care and treatment, preparation for the patient's discharge, and follow-up care plans at home. There is a relationship between family support and anxiety levels in pre-operative patients at dr. Soepraoen Hospital